Can training bar staff in responsible serving practices reduce alcohol-related harm? - Lang, E.; Stockwell, Tim; Rydon, P.; Beel, A. (Taylor and Francis, 1998)
A responsible service training programme aimed at reducing alcohol-related harm was implemented in a popular entertainment area over several months in 1992-93. Another popular entertainment area provided a control site. A number of evaluation measures were used: breath tests on 872 patrons from selected venues; drink driving data; risk assessments; the use of 'pseudo patrons'; and knowledge and attitude changes among trained bar staff (n = 88). Compared to control sites the intervention sites showed an immediate pre- to post-test reduction in patrons rated by researchers as extremely drunk and an eventual reduction from pre-test to follow-up in patrons with blood alcohol levels > = 0.08. There was also a small but significant increase in knowledge among bar staff. There was no significant reduction in patrons with blood alcohol levels > = 0.15 or in the number of drink driving offences from intervention sites during the study period. Pseudo drunk patrons were rarely refused service, identification was rarely checked and non-photographic identification was accepted on most occasions. The less than satisfactory outcome is attributed to poor implementation of the training and a lack of support among managers. The positive results from one venue, whose manager embraced the programme, served to highlight the importance of management support. It is suggested that mandatory training and routine enforcement of licensing laws are essential if the goals of responsible serving are to be met.